2 Del. Laws 1134 (1797) - (:unkn) unknown (My University, 1793)
Included " each and every free able bodied white male citizen of this state, who is or shall be of the age of eighteen years, and under the age of forty-five years." However, " all young men under the age of twenty-one years, and all servants purchased bona fide, and for a valuable consideration, [were] exempted from furnishing the necessary arms, ammunition and accoutrements . . . and [were] exempted from militia duties and fines during such minority or servitude, except in cases of rebellion, or an actual or threatened invasion."
Keywords: MILITIAS; ENSLAVED PERSONS AND OTHER MINORITIES